Exploration of STEM integration on student achievement in madrasah science competition: Qualitative approach - Siregar, Nur Choiro; Warsito, Warsito; Rosli, Roslinda (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study explores the impact of STEM integration on student performance in the Madrasah (school) Science Competition (KSM), focusing on how STEM-based learning enhances academic achievement. The growing importance of STEM education globally emphasizes its potential to improve students' scientific knowledge and critical thinking. Integrating STEM in Madrasah education, mainly through science competitions like the Madrasah Science Competition (KSM), challenges students to apply theoretical knowledge in practical, real-world contexts. Despite the increasing interest in STEM education, researchers have yet to fully understand its specific impact on student performance in KSM, particularly within the context of Islamic schools. Here, we examine how STEM integration affects student achievement in KSM. The research employs a qualitative approach, using thematic analysis to analyze open-ended questioning with students who participated in KSM. The results reveal that STEM integration on student achievement in KSM resulted in (a) scientific inquiry and problem-solving, hands-on experimentation, theoretical knowledge application, (b) use of technology and tools, and resource disparities, (c) increased engagement through STEM, and confidence in problem-solving, (d) limited access to resources, (e) collaborative learning in STEM projects, and team dynamics and support, (f) enhanced scientific understanding, and development of critical thinking skills, (g) improved KSM outcomes, and increased interest in science careers. The implications suggest incorporating STEM into Madrasah curricula can enhance academic achievement and foster critical thinking skills. Future research could explore the long-term impact of STEM integration on broader educational outcomes and investigate ways to scale STEM practices across Madrasah institutions.